2018
DOI: 10.1002/lary.27775
|View full text |Cite
|
Sign up to set email alerts
|

Lingual tonsil lymphatic tissue regrowth in patients undergoing transoral robotic surgery

Abstract: Objectives/Hypothesis: To evaluate a possible regrowth of lingual tonsil lymphatic tissue in patients submitted to lingual tonsil resection with transoral robotic surgery (TORS).Study Design: Retrospective Study. Methods: Medical records of patients surgically treated by means of TORS to remove excessive lymphatic tissue of the lingual tonsil were retrospectively reviewed. Postoperative endoscopic data after long-term follow-up were analyzed to investigate possible lymphatic tissue regrowth. Preoperative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Elderly patients with OSA could show changes in OSA related parameters (AHI, ODI SpO2, etc), OSA symptoms, time of sleep and pattern/type of collapse [2][3][4][5][6][7][8][9][10][11][12]. Aging is associated with a lengthening of the upper airway and descent of the hyoid bone [32][33]. The response of the genioglossus muscle to negative pressure is also reduced in older people compared to younger peopl and less negative pressure is required to collapse the upper airway, independent of BMI in older people [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly patients with OSA could show changes in OSA related parameters (AHI, ODI SpO2, etc), OSA symptoms, time of sleep and pattern/type of collapse [2][3][4][5][6][7][8][9][10][11][12]. Aging is associated with a lengthening of the upper airway and descent of the hyoid bone [32][33]. The response of the genioglossus muscle to negative pressure is also reduced in older people compared to younger peopl and less negative pressure is required to collapse the upper airway, independent of BMI in older people [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Different methods of meta-analysis were considered in reviewing the literature to seek results that would provide meaningful analysis with the least risk of introducing biases. The quality assessment of studies (QUADAS-2) tool was used to evaluate the relevant study design characteristics of the included studies [32].…”
Section: Meta-analysis Protocolmentioning
confidence: 99%
“…In adults, the procedure of reducing lingual tonsil through Trans Oral Robotic Surgery (TORS) is widely used. In children, it is not a common procedure [38,39]. In particular, the young patient of Figure 3 underwent robotic surgery due to severe OSAS with disabling symptoms without adenotonsillar hypertrophy or other risk factors.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Finally, the myofunctional therapy (MFT) with its active training of the oropharyngeal muscles has been introduced as an OSA treatment modality. The current studies demonstrate a positive effect in reducing sleep apnea, as shown by the post-therapy improvement of polysomnography values and clinical symptoms [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
mentioning
confidence: 60%
“…In this scenario, barbed reposition pharyngoplasty (BRP), devised by Vicini et al [ 22 ], showed excellent outcomes at short- and long-term follow-up [ 23 , 24 ]. Another surgical option, which gave optimal anatomical and functional results [ 25 , 26 ], is the transoral robotic surgery utilized for the base of tongue resection.…”
mentioning
confidence: 99%